High nitrate levels in skeletal muscle contribute to nitric oxide generation via a nitrate/nitrite reductive pathway in mice that lack the nNOS enzyme - Upanan, Supranee; Lee, Jeeyoung; Tunau-Spencer, Khalid J.; Rajvanshi, Praveen K.; Wright, Elizabeth C.; Noguchi, Constance T.; Schechter, Alan N. (Frontiers in Physiology, 2024)
Introduction: Nitric oxide (NO) is a vasodilator gas playing a critical role in mitochondrial respiration and skeletal muscle function. NO is endogenously generated by NO synthases: neuronal NO synthase (nNOS), endothelial NO synthase (eNOS), or inducible NO synthase (iNOS). NO in skeletal muscle is partly generated by nNOS, and nNOS deficiency can contribute to muscular dystrophic diseases. However, we and others discovered an alternative nitrate/nitrite reductive pathway for NO generation: nitrate to nitrite to NO. We hypothesized that nitrate supplementation would increase nitrate accumulation in skeletal muscle and promote a nitrate/nitrite reductive pathway for NO production for loss of nNOS in skeletal muscle. Methods: Wild-type (WT) and genetic nNOS knockout (nNOS-/-) mice were fed normal chow (386.9 nmol/g nitrate) and subjected to three treatments: high nitrate water (1 g/l sodium nitrate for 7 days), low nitrate diet (46.8 nmol/g nitrate for 7 days), and low nitrate diet followed by high nitrate water for 7 days each. Results: High nitrate water supplementation exhibited a greater and significant increase of nitrate levels in skeletal muscle and blood in nNOS-/-mice than in WT mice. Low nitrate diet decreased blood nitrate and nitrite levels in both WT and nNOS-/-mice. WT and nNOS-/-mice, treated with low nitrate diet followed by high nitrate water supplementation, showed a significant elevation in nitrate levels in skeletal muscle and blood, analogous to the increases observed in nNOS-/-mice supplemented with high nitrate water. In skeletal muscle of nNOS-/-mice on high nitrate water supplementation, on low nitrate diet, and in low-high nitrate treatment, the loss of nNOS resulted in a corresponding increase in expression of nitrate/nitrite reductive pathway-associated nitrate transporters (sialin and chloride channel 1 (CLC1)) and nitrate/nitrite reductase (xanthine oxidoreductase (XOR)), but did not show a compensatory increase in iNOS or eNOS protein as well as eNOS activation activity (p-eNOS (Ser1177)). Discussion: These findings suggest that a greater increase of nitrate levels in skeletal muscle of nNOS-/-mice on nitrate supplementation results from reductive processes to increase NO production with the loss of nNOS in skeletal muscle.